Design, Synthesis and Characterization of Palladium‐Functionalized Covalent Organic Framework and Its Application as Heterogeneous Catalysis for C−H Arylation of Azoles - Li, Wen‐Jing; Chen, Yu‐Xuan; Kang, Shi‐Long; Mo, Li‐Ping; Zhang, Zhan‐Hui (Chemistry : a European journal, 2023)
A novel triazine‐based covalent organic framework (TFPT‐Bz COF) has been constructed by the condensation of 2,4,6‐tris(5‐formyl‐2‐pyridinoxy)‐1,3,5‐triazine (TFPT) and benzidine (BZ) with deep eutectic solvent (DES) as the reaction medium. After the introduction of Pd ions through strong coordination to TFPT‐Bz COF matrix, the constructed TFPT‐Bz COF/Pd composite exhibited excellent catalytic activity for C−H arylation of azoles with aryl halides in 2‐methyltetrahydrofuran. The protocol allows the arylation of a variety of substituted azoles with diverse aryl halides in high to excellent yield. Moreover, the TFPT‐Bz COF/Pd catalyst can be recycled several times without significantly reducing its activity. A palladium‐functionalized covalent organic framework with high thermal and chemical stabilities has been prepared and used as heterogeneous ligand to immobilize PdII. The resulting Pd‐bound COF was found to be an efficient heterogeneous catalyst for the C−H arylation of azoles and aryl halides with high recyclability.